Inflammation and immune cell entry to the central nervous system - Rivest, Serge (Henry Stewart Talks, 2008)
Systemic infection and blood sepsis, Toll-like receptors and proinflammatory signaling in microglia, Brain diseases associated with inflammation, Innate immunity and neuroprotection
Reviewed at 2017/05/24